A computer simulation study of OH defects inMg2SiO4 and Mg2GeO4 spinels - Wright, Kathleen; Gale, Julian; Blanchard, M. (Springer, 2005)
Classical atomistic simulation techniques have been used to investigate the energies of hydrogen defects in Mg2SiO4 and Mg2GeO4 spinels. Ringwoodite (c-Mg2SiO4) is considered to be the most abundant mineral in the lower part of the transition zone and can incorporate large amounts of water in the form of hydroxyls, whereas the germanate spinel (c-Mg2GeO4) corresponds to a low-pressure structural analogue for ringwoodite. The calculated defect energies indicate that the most favourable mechanisms for hydrogen incorporation are coupled either with the reduction of ferric iron or with the creation of tetrahedral vacancies. Hydrogen will go preferentially into tetrahedral vacancies, eventually leading to the formation of the hydrogarnet defect, before associating with other negatively charged point defects. The presence of isolated hydroxyls is not expected. The same trend is observed for germanate, and thus c-Mg2GeO4 could be used as a low-pressure analogue for ringwoodite in studies of water-related defects and their effect on physical properties.